Legal Analysis of the Impact of Law Enforcement on Fraud Perpetrators in the JKN Program - Wulandari, Anggi Yudistia (Faculty of Law, University of Mataram, 2025)
BPJS Kesehatan, which runs the JKN programme, has the largest number of participants in Indonesia, with 98.21% of the Indonesian population enrolled as of 1 June 2025. The objective of the JKN programme is to provide the public with access to affordable and quality health services. There are many debates and issues faced in maintaining the sustainability of the JKN programme, one of which is fraud committed by health facilities. The absence of sanctions or firm action against perpetrators of fraud encourages them to repeat their actions. This study aims to analyse the effect of law enforcement on perpetrators of fraud. This study uses a normative juridical method with a statute approach and a conceptual approach. The research approach was conducted by examining various legal reference materials (secondary data). The results of the study show that law enforcement against fraud perpetrators as stipulated in Minister of Health Regulation (Permenkes) No. 16 of 2019 has not had a deterrent effect and taken firm action against perpetrators because the sanctions imposed are only administrative in nature, such as verbal and written warnings, compensation and revocation of licences, and the types of fraud that need to be updated. Based on legal analysis, efforts are needed to reform sanctions against fraud perpetrators and to clearly divide tasks among PK JKN team members. Support from the entire JKN ecosystem is also needed in enforcing sanctions against fraud perpetrators. Stronger regulations will reduce the desire to commit fraud in JKN and combat fraud.